A study on supplementary factors that influence the human development index - Carangian, Gabrielle S.; Ugay, Jamielynne D.
The Human Development Index is an important measure to keep track of a country's development based on three dimensions: health, education, and standards of living. The HDI, however, remains an inadequate index of development as it is a reductionist measure that does not take into account other important aspects of development. This study started off by identifying the supplementary factors that can possibly affect the HDI, namely poverty, inflation, unemployment, and population. Ordinary Least Squares (OLS) regression and the fixed effects model are used to determine the relative importance between HDI and the four variables. The researchers found that poverty negatively and population positively affects the HDI. Other variables namely, inflation and unemployment are not significant to HDI. Based on these results, alleviating poverty through government programs such as the 4Ps, and ensuring simultaneous quantity and quality improvements in the population are suggested to boost human development growth.